The Attitude of Students and the Mediating effect of Acceptance, Interactivity and LMS on Integration of Technology - Yaw Odame Gyau; Ernest Kwabena Gyan; Stanley Kwame Marcus Semarco (Noyam Journals, 2023)
Although the phenomenon of technology is gradually being integrated into tertiary education in Ghana, the perceptions of students to adopt and adapt to learning technologies for smooth integration of technology into academic programmes in public universities is an issue of concern. Using the Constructivist and Positivist paradigm, this study adopted the quantitative approach and the purposive and quota sampling technique to solicit data from 1704 level 400 students in six (6) accredited public universities. Adopting the regression analyses approach with ten hypotheses tested the results were analyzed with PLS-SEM. The study found that the attitudes of students significantly impact the integration of technology. Indirectly, Students' Acceptance and Adjustment (AA) to use technology and Learning Management System (LMS) usage significantly mediates the relationship between the Attitude of Students (AS) and the Integration of technology (IG). Furthermore, students' acceptance and adjustment to adopt technology and the use of the LMS, are key predictors of the integration of technology, but Interactivity is a weak predictor of the integration of technology into academic programmes in the topmost public universities in Ghana.